PROGRAM VIDEO CALL BERBASIS PEER TO PEER MENGGUNAKAN PROTOKOL RTMFP - Nathaniel Gunawan; Gani Indriyanta; Willy Sudiarto Raharjo (Universitas Kristen Duta Wacana, 2015)
The rapid development of information technology-based communication to encourage the development of video conferencing applications to a variety of media platforms. One of the media that is easily accessible is a web application development based RIA (Rich Internet Application). In this study developed a flash-based video conferencing application to utilize the net class group in ActionScript 3.0 and multimedia protocols RTMFP (Real Time Media Flow Protocol). Streaming video delivery technology requires codecs to be able to transmit video and audio. To find out which one is suitable codec in the development of this application, the analysis is done where appropriate codec for video conferencing on the public network access in terms of the quality of the resulting. The conclusion of the implementation and analysis of three types of audio codecs and codec, is that the codec h.264 and h.264 base profile play a video codec that is suitable for public networks because it produces little noise when there is a lot of movement when compared to the Sorenson video codec.